2022
DOI: 10.3390/ani12101279
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and Prevalence of Antibiotic-Resistant Bacteria: A Study of 398 Pet Reptiles

Abstract: Reptiles are potential reservoirs of bacteria that could be transmitted, thus becoming a zoonotic hazard. (1) Background: This three-year investigation surveyed the pathological status of 398 pet reptiles: chelonians, snakes (venomous/non-venomous), and lizards. The main pathological entities found were related to the skin, the sensory organs, the digestive system, the respiratory system, the cardiovascular system, the urinary system, the genitalia, the osteo–muscular tract, surgical issues, tumors, and intoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Six percent of human Salmonellosis cases are acquired after interactions with reptiles, and the intimate contact between reptiles and their owners creates favorable conditions for the transfer of zoonotic pathogen infections [1][2][3]. In addition, Salmonella strains discovered from pet reptiles have been linked to antibiotic resistance, one of the most serious health issues of the twenty-first century that may have therapeutic repercussions for reptile owners and breeders [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Six percent of human Salmonellosis cases are acquired after interactions with reptiles, and the intimate contact between reptiles and their owners creates favorable conditions for the transfer of zoonotic pathogen infections [1][2][3]. In addition, Salmonella strains discovered from pet reptiles have been linked to antibiotic resistance, one of the most serious health issues of the twenty-first century that may have therapeutic repercussions for reptile owners and breeders [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The diminution of neutrophils does not infirm the phagocytes activity by BV because these can be a qualitative state, that is an increase of phagocytic capacity not on the rise of cell number, but on basis of the biochemical functional enhancement of those cells' availability or may be indirect through the activation of particles opsonization or of other internal medium physical-chemical conditions. 42 A significant increase was observed in RBCs count, WBCs count, platelets count, Hb concentration, and PCV value on regular treatment with BV when compared with the control animals. 43 In addition, regarding the effect of BV on the platelet count, the data obtained in this study showed a non-significant decrease.…”
Section: Discussionmentioning
confidence: 83%
“…Weitzman et al ( 2018 ) analysed cutaneous microbiota on lizards and found Pseudomonadales, Actinomycetales, Burkholderiales, Sphingomonadales, Rhizobiales and Enterobacteriales to be the most abundant orders. The study of Cristina et al ( 2022 ) determined E. faecalis as the most frequently isolated species; however, their study included 25 sick reptiles with no response to treatment. The identification of the Salmonella genus in Elaphe schrenckii confirms the fact that reptiles are well-known reservoir of Salmonella , species as previous studies also demonstrated (Zajac et al 2021 ; Dégi et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also necessary to mention the fact that the given dosages of antimicrobials are either extrapolated from human medicine or empirically assumed according to the reptile species, which could lead to a lack of a proper anti-infective agents for the particular pathology of reptiles. Based on the fact that antimicrobial resistance is a gradually increasing phenomenon in reptiles (Cristina et al 2022 ), the completion of an antibiogram is a current and reliable method to combat resistance.…”
Section: Discussionmentioning
confidence: 99%